Propriedades vibracionais do ácido oxálico dihidratado em altas pressões - Rufino, Francisco Marciano (2019)
Dicarboxylic acids are organic compounds which have in their structure two carboxyl functional groups whose molecule form can be written as (HOOC-R-COOH), where R is a radical which differentiates each acid from the family and may be an alkane, alkene or alkyne. Each acid can be found in more than one crystalline form. Oxalic acid (C​2​H​2​O​4​), the simplest acid in the family, can be found in four forms, two anhydrides and two di-hydrates. The ɑ-oxalic acid dihydrate (AODɑ), whose chemical formula is C​2​H​2​O​4​ .2H​2​O, object of study of this work, has been studied for about a century and has led to discussions about the hydrogen bonding behavior between the oxalic acid molecule and the water molecule and is related to changes in the crystalline structure under pressure. AODɑ crystals were grown by the slow evaporation method using distilled water as the solvent. Its crystalline structure was confirmed to be monoclinic with space group P2 1 / n, Z = 2, and lattice parameters a = 6,1026 A, b = 3,4867 A, c = 11,954 A, β = 105,79​0​ by means of the X-ray diffraction technique with the powder obtained from the maceration of part of the crystalline sample, with which the Rietveld refinement method was used. A Raman spectroscopy experiment was performed in two distinct polarizations under ambient conditions and the classified vibrational modes. In order to study the stability of the crystal under high hydrostatic pressures, two experiments were performed. Experiment I achieved pressures of up to 14.0 GPa using nujol as the pressure transmitting fluid and Experiment II reached pressures of up to 24.4 GPa using the neon gas as a pressure transmitting fluid. Modifications in both external and internal modes indicate that the sample undergoes at least four reversible phase transitions. The main objective of this work is to study the stability of AODɑ crystal under extreme pressure conditions through two experiments and to compare with the results of works that explored the role of hydrogen bonds, since these directly influence the stability of structures in which are present.